Kinerja Simpang Bersinyal BTP – Perintis Kemerdekaan – Lingkar Barat Kota Makassar - Imanuel Egi Kabangnga; Rais Rachman; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2023)
At the intersection of BTP – Perintis Kemerdekaan – West Ring has experienced a long queue of vehicles, especially the Perintis Kemerdekaan road, from the south to the north of the vehicle queue to door 2 of UNHAS while from the opposite direction the queue of vehicles occurs until the Regional Library and Archives Office of South Sulawesi Province. Vehicle queues occur during peak hours. This study aims to determine the saturated current, capacity, and degree of saturation of the BTP – Pioneer of Independence – West Ring interchange at the peak hour of morning or evening existing conditions, as well as the relationship between capacity to the degree of saturation at the BTP – Pioneer of Independence – West Ring interchange. To calculate traffic flow, vehicles divided into 4 namely Light Vehicles, Medium Vehicles, Motorcycles, and Non-Motorized Vehicles are not considered part of the traffic flow but side obstacles. The method used in this study is in accordance with PKJI 2014. From the data and results of research conducted manually on the performance of the interchange that brings together BTP, Jalan Perintis Kemerdekaan and Jalan Lingkar Barat, it was found that the degree of saturation of intersection performance is included in category C. According to the Indonesian Road Capacity Guidelines, the results of this study can be said that the condition of the interchange traffic flow that brings together BTP, Independence Pioneer Road and West Ring Road The current is stable but the speed and motion of vehicles Controlled.